The devil is a part-timer! 11 - Wagahara, Satoshi (Yen Press, 2018)
"When Chiho collapses, Maou and the others conclude it must be the work of an angel. All that's left is to figure out whether their assailant is hold up in Tokyo Tower or the Skytree before dispatching the Maou/Alciel dream team to take them down! Meanwhile, will the tiny Devil's Castle be able to make the transition to digital television?!"--Page 4 of cover.